2012
DOI: 10.1177/0037549712444121
|View full text |Cite
|
Sign up to set email alerts
|

Grid Matrix: a grid simulation tool to focus on the propagation of resource and monitoring information

Abstract: Grid Computing proposes unlimited access to different computational resources in a transparent way. High performance execution in grid environments is virtually impossible without timely access to accurate and up-to-date information related to distributed resources and services. Due to inherent difficulty of testing the different information propagation policies in real grid infrastructures, several simulation frameworks arose to help in this issue. In this work, we present Grid Matrix, an extension to one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This function involves an implicit relation between their weighting coefficients (see Materials and Methods for details). The selection of each weight in this relation leads to focusing on some of the aspect of the system, in this work a standard set of parameters were used following previous works [19,20,14]. Using the standard scoring function, the scoring function may select a node that do not have much proper information and instead has lots of data about its neighbors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…This function involves an implicit relation between their weighting coefficients (see Materials and Methods for details). The selection of each weight in this relation leads to focusing on some of the aspect of the system, in this work a standard set of parameters were used following previous works [19,20,14]. Using the standard scoring function, the scoring function may select a node that do not have much proper information and instead has lots of data about its neighbors.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these results, in Mocskos et al [14] some good initial results of this policy were shown. Best-neighbor get good performance and, mainly, the overall information known by the system increases with time.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations